Estimativa sorológica de risco de transmissão transfusional de toxoplasma Gondii - Paduan, Natália Juliana (2017)
The prevention of transmission of pathogenic microorganisms by transfusion of blood components results from a combination of different transfusion safety procedures. Despite the continuous improvement of these safety procedures, there are still risks of transfusional transmission of infectious and parasitic diseases and different facts may contribute to these risks. Among the microorganisms potentially capable of being transmitted by blood transfusion and blood components are Toxoplasma gondii. The screening of this parasite is not compulsory in Brazilian blood donors and, therefore, the risks related to its transfusion transmission are unknown. Material and Method. We selected 1,729 blood donors from the Regional Blood Center from São José do Rio Preto – SP, of both genders, eligible for donation. Serum samples were used for the detection of anti-T. gondii antibodies IgM and IgG with the use of the ELISA method. Four groups were composed according to the serological profiles: G1: IgM non-reactive and IgG non-reactive; G2: IgM reactive and IgG reactive; G3: IgM reactive and IgG non-reactive; G4: IgM non-reactive and IgG reactive. All blood components units were monitored to determine the risk of transfusion of T. gondii. The t-test was used to compare age averages according to gender and with the "reactive" and "non-reactive" condition. The prevalence of infection was determined by direct counting. Odds Ratio and 95% confidence intervals were also calculated. The p value adopted was equal to 5%. Results. The prevalence of infection in blood donors in the northwest region of the State of São Paulo was 48.3% (835/1,729), being high in both genders. The serological profile of acute infection (IgM reactive/IgG non- reactive) was identified in only 0.46% (8/1,729) of the analyzed donors. The risk of transfusion of the parasite by means of blood components was 2%. Conclusion. The prevalence of infection by T. gondii in blood donors of both genders is high in the northwest region of the State of São Paulo. The serological profile of acute infection was similar to those observed in other Brazilian regions and in other countries. The risk of transmission in transfusion of T. gondii by blood components is low in the northwest region of the State of São Paulo.